Reconstructive surgery for deep vein reflux - Perrin, M. (Phlebologie, 2014)
DVR is defined as a reflux affecting the deep venous system. DVR essentially arises from two etiologies, primary deep valve incompetence (PDVI) and posthrombotic syndrome (PTS), knowing that axial reflux is correlated with severe chronic venous insufficiency. DVR correction aims at reducing the increased ambulatory venous pressure, which results from reflux in deep veins in orthodynamic conditions.The results of DVR surgery are not easy to assess, as it is mostly combined with surgery for superficial venous system and/or perforators insufficiency.In cases of primary insufficiency, valvuloplasty, the operation of choice, is credited at 5 years follow-up with a 70 % success rate in terms of clinical outcome and improved hemodynamic performance. In PTS, a meta-analysis of transpositions and transplants at more than 5 years estimates successful clinical outcome and improved hemodynamic performance at approximately 50 %. The Maleti neovalve construction technique has achieved by far better results.Indications for DVR surgery are based on clinical, hemodynamic and imaging data. Etiology is a decisive factor in the choice of the technique.
Keywords: Deep venous surgery; venous valve incompetence; chronic venous insufficiency; venous reflux; post-thrombotic syndrome